Graphene on nickel (100) micrograins: Modulating the interface interaction by extended moiré superstructures - Zou, Zhiyu (2018)
Interaction with the substrate strongly affects the electronic/chemical properties of supported graphene. So far, graphene grown by chemical vapor deposition (CVD) on catalytic single crystal transition metal surfaces - mostly 3-fold close-packed - has mainly been studied. Herein, we investigated CVD graphene on a polycrystalline nickel (Ni) substrate, focusing in particular on (100) micrograins and comparing the observed behavior with that on single crystal Ni(100) substrate. The symmetry-mismatch leads to moiré superstructures with stripe-like or rhombic-network morphology, which were characterized by atomically-resolved scanning tunneling microscopy (STM). Density functional theory (DFT) simulations shed light on spatial corrugation and interfacial interactions: depending on the misorientation angle, graphene is either alternately physi- and chemisorbed or uniformly chemisorbed, the interaction being modulated by the (sub)nanometer-sized moiré superstructures. Ni(100) micrograins appear to be a promising substrate to finely tailor the electronic properties of graphene at the nanoscale, with relevant perspective applications in electronics and catalysis.